Molecular characterization of medulloblastomas with extensive nodularity (MBEN) - Korshunov, Andrey; Sahm, Felix; Stichel, Damian; Schrimpf, Daniel; Lichter, Peter; Jones, David T. W.; Deimling, Andreas von; Pfister, Stefan; Kool, Marcel (Acta neuropathologica, 2018)
Medulloblastoma with extensive nodularity (MBEN) is a rare histological variant of medulloblastoma (MB). These tumors are usually occurring in the first 3 years of life and are associated with good prognosis. Molecular analyses of MBEN, mostly limited to single cases or small series, have shown that they always classify as sonic hedgehog (SHH)-driven MB. Here, we have analyzed 25 MBEN through genome-wide DNA methylation, copy-number profiling and targeted next-generation sequencing.
Gesehen am 22.01.2020